2001
DOI: 10.1021/jp0040704
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and NMR Study of the α(1→4) and α(1→6) Glycosidic Linkages:  Maltose and Isomaltose

Abstract: We report the results of molecular dynamics (MD) simulations compared with NMR relaxation experiments for maltose and isomaltose. The (Φ,Ψ) adiabatic map for maltose shows a single principal energy well, while the (Φ,Ψ,Ω) map of isomaltose reveals multiple low energy minima separated by significant barriers (9 kcal/mol) in some cases. The greater accessible conformational space of the α(1→6) linkage appears to make it more flexible as compared with the α(1→4) linkage, especially in the presence of water. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 56 publications
(114 reference statements)
6
76
0
Order By: Relevance
“…67 However, as in the present case, effects of anisotropic diffusion must be separated from contributions due to internal motion before conclusions about the latter can be drawn.…”
mentioning
confidence: 77%
“…67 However, as in the present case, effects of anisotropic diffusion must be separated from contributions due to internal motion before conclusions about the latter can be drawn.…”
mentioning
confidence: 77%
“…5 (see Section 4) and compared with the values derived from experimental relaxation parameters. 13 As can be seen from Figure 3, the values for the C-H vectors in the six-membered rings are relatively large indicating that maltose and its sixmembered glycosyl unit are quite rigid. Due to greater freedom of motion, in the simulation the C-6-H-6 and C-6 0 -H-6 0 vectors have much lower order parameters than those within the ring, while in the experiment the C-6-H-6 and C-6 0 -H-6 0 vectors have order parameters comparable to those within the ring.…”
Section: Force-field Testingmentioning
confidence: 92%
“…Molecular dynamics (MD) simulation studies of carbohydrates in the literature 10;11 deal with maltose or cellobiose composed of two glucose units [12][13][14][15][16] or with cyclic chains including a-, b, and c-cyclodextrins [17][18][19][20][21][22][23] as well as the single glucose units of a-and b-anomers. 15;24;25 However, there are only a few studies dealing with longer amylose or cellulose chains.…”
Section: Introductionmentioning
confidence: 99%
“…1). On the other hand, Best et al found that isomaltose exhibited multiple low-energy minima, with more flexible and more extended conformations in water compared with maltose in the MD simulations and NMR relaxation experiments [4], indicating that the torsion angle of glycosidic linkages in isomaltose is rather variable.…”
Section: Unique Torsion Angles Of Constituent Disaccharides Affect Vumentioning
confidence: 99%